Serological Protection Rates against TBEV Infection in Blood Donors from a Highly Endemic Region in Southern Germany - Gerhard Dobler; Kathrin Euringer; Klaus Kaier; Johannes P. Borde (Vaccines, 2023)
Background: Tick-borne encephalitis (TBE) is the most significant tick-borne disease in Europe and Asia, with more than 10,000 cases per year worldwide. A surge of reported TBE cases can be observed despite the availability of highly efficient vaccines. There is little known about the serological immune protection rate of the population in Germany. The seroprotection rate is defined as the presence of neutralizing antibodies. In contrast, the vaccination rate, as defined by public health agencies, may differ from the true protection rate in a population. Materials and Methods: 2220 blood samples from inhabitants of the county Ortenaukreis in the Federal State of Baden-Württemberg in Germany were included in the study. These were tested for anti-TBEV IgG antibodies by an anti-TBEV-IgG-ELISA. Subsequently, all TBEV-IgG positive samples were confirmed for neutralizing antibodies in the micro serum neutralization assay. Results: From the overall 2220 samples, 2104 were included in the comparison because of the selection of specific age groups (ages 20–69). In our sample size, we found an average serological protection rate (presence of neutralizing antibodies) of 57% (518/908) for the female blood donors and of 52% (632/1196) for the male blood donors. Discussion: In this study, we present new findings on a highly endemic region in southern Germany. Additionally, we present current data regarding the serological TBEV protection rates in the Ortenaukreis in southern Germany and compare these with a dataset published by the RKI, which is based on vaccination reports of the primary care providers and health care insurers, and with a self-reporting study conducted by a vaccine manufacturer. Our results significantly exceed the official numbers of average active vaccination status by 23.2% for females and by 21% for males. This might indicate an even longer persistence of TBE-vaccination-induced antibody titers than previously assumed.